The senotherapeutic nicotinamide riboside raises platelet nicotinamide adenine dinucleotide levels but cannot prevent storage lesion. Issue 1 (25th October 2019) - Delabie, Willem; Maes, Wim; Devloo, Rosalie; Van den Hauwe, Michelle R.; Vanhoorelbeke, Karen; Compernolle, Veerle; Feys, Hendrik B.
Abstract : BACKGROUND: Supplementation of the nicotinamide adenine dinucleotide (NAD) precursor nicotinamide riboside (NR) has recently been shown to increase life‐span of cells, tissues, and entire organisms. [Correction added on 13 December 2019, after first online publication: In the preceding sentence, "adenine nicotinamide" was revised to "nicotinamide adenine."] The impact of NR on platelet longevity has not been tested. STUDY DESIGN AND METHODS: A pool‐and‐split design of buffy coat derived platelet concentrates (PCs) was used. One arm was treated with cumulative doses of NR‐triflate, the control arm with sodium triflate. Storage lesion was monitored for 23 days. Platelet metabolic and functional parameters were tested. Clearance of human platelets was measured in a mouse model of transfusion. RESULTS: Total intracellular NAD levels in platelets decreased two‐fold from 4.8 ± 0.5 fmol (mean ± SD, n = 6) to 2.1 ± 1.8 fmol per 10 3 control cells, but increased almost 10‐fold to 41.5 ± 4.1 fmol per 10 3 NR treated platelets. This high intracellular NAD level had no significant impact on platelet count, mean platelet volume, swirling, nor on lactate and glucose levels. Platelet aggregation and integrin αIIb β3 activation declined steadily and comparably in both conditions. GPIbα levels were slightly lower in NR‐treated platelets compared to control, but this was not caused by reduced receptor shedding because glycocalicin increased similarly. Apoptotic markers cytochrome c, Bcl‐xL, cleaved caspase‐3, and Bak were not different throughout storage for both conditions. Platelet survival in a mouse model of transfusion was not different between NR‐treated and control platelets. CONCLUSION: Platelets carry the cellular machinery to metabolize NR into NAD at rates comparable to other eukaryotic cells. Unlike those cells, platelet life‐span cannot be prolonged using this strategy.